Investigation of Cytotoxic and Genotoxic Properties of Hybrid Compounds Containing New Generation Amino Acid Structures - Sekerci, Guldeniz; Yuksel, Furkan; Tekin, Suat; Caliskan, Eray; Biryan, Fatih; Koran, Kenan; Sandal, Suleyman (Wiley, 2023)
[Abstract Not Available]
Keywords: Amino acid-coumarin; Caco-2; MTT Assay; Comet Assay